ANALISIS HUKUM TERHADAP PENGUNAAN FAKTUR PAJAK YANG TIDAK BERDASARKAN TRANSAKSI SEBENARNYA YANG DILAKUKAN OLEH WAJIB PAJAK BESERTA KONSULTAN PAJAK PERUSAHAAN: KONSULTAN PAJAK PERUSAHAAN - Yohanes Supriyono (JEKOS (Jurnal Ekonomi Dan Sosial), 2025)
According to Article 39A of Law No. 6 of 1983 concerning General Provisions and Tax Procedures as last amended by Law No. 11 of 2020 concerning Job Creation, it states that if any person intentionally issues a fictitious Tax Invoice will be subject to criminal sanctions of at least 2 years and a maximum of 6 years and a fine of at least 2 times the amount of tax in the tax invoice and a maximum of 6 times the amount of tax in the tax invoice. The Director in this case is the person responsible for the PT taxpayer who must face criminal charges and the threat of confiscation of losses both materially and immaterially. The rampant manipulation of tax invoices that are made not in accordance with actual transactions that are detrimental to the state and for the sake of just law enforcement, and legal certainty for taxpayers in this case the Directors of a company who are responsible for issuing tax invoices and reporting VAT SPTs should be handled more wisely. The method used by the author in this study uses the Normative research method. In this study the author uses the Theory of Legal Certainty, Legal Protection and Justice Theory. The research results show that to resolve tax disputes, taxpayers can pursue several avenues, including lawsuits, appeals, and even cassation appeals to the Supreme Court. All of these efforts are intended to foster a sense of justice for the public and foster public trust as taxpayers in the performance of the Directorate General of Taxes, as well as the principle underlying tax collection for the greatest possible prosperity of the people. Furthermore, in Decision 33/Pid.Sus/2021/PN JKT.SEL, the Judge failed to consider the legal facts: Edwar Hasan is the President Director of PT. Rajawali Kreasi Mandiri, Romi Rosa is a commissioner, and ERSA KARSIA is the Sales Manager. Furthermore, PT. Rajawali Kreasi Mandiri is a legal entity and is a Corporate Taxpayer subject to the Limited Liability Company Law, which can apply joint and several liability.   Keywords: Tax Invoice, Taxpayer, Tax Consultant.